Rare earth aluminum garnet sintered body and its manufacturing method, Faraday element, and magneto-optical element
Patent Information
- Application Number
- JP2020143778
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-08-27
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-08-27
AI Technical Summary
【0027】 本発明によれば、波長1μm帯のレーザー光に対してヴェルデ定数(VC)及び消光比が高いとともに吸収係数が小さい希土類アルミニウムガーネット焼結体、及びこの焼結体を備えたファラデー素子が提供される。また本発明によれば、上記焼結体及びファラデー素子を低コストで製造する方法が提供される。更に、上記ファラデー素子を備えた磁気光学素子が提供される。
Smart Images

Figure 0007608752000007 
Figure 0007608752000008 
Figure 0007608752000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a rare earth aluminum garnet sintered body and a method for producing the same, a Faraday element, and a magneto-optical element. [Background technology]
[0002] In recent years, the power output of lasers has increased, and the use of laser processing has expanded accordingly. Fiber lasers (FL) with a wavelength of 1 μm (0.9 to 1.1 μm) are used in laser processing. Fiber lasers are a type of solid-state laser that uses an optical fiber doped with ytterbium (Yb) as a medium, and are characterized by easy focus design, good amplification efficiency, easy cooling, and high output. In fiber lasers, the laser light emitted from a semiconductor laser is input to one end of an optical fiber, and its intensity is amplified hundreds to thousands of times while passing through the optical fiber. The laser light emitted from the other end of the optical fiber reaches the object to be processed, where the laser processing is performed. The emitted laser light is characterized by high quality and being close to single mode.
[0003] In fiber laser processing, a portion of the laser light that reaches the workpiece may be reflected and return to the optical fiber, i.e., return light may occur. When such return light occurs, it is further amplified as it passes back through the fiber and reaches the semiconductor laser. The amplified return light not only makes the laser oscillation unstable, but it may also destroy the semiconductor laser. To prevent such problems, in fiber laser processing, an optical isolator (OI) that blocks return light is generally provided at the optical output section.
[0004] Conventionally, the Faraday element for optical isolators has been made of Tb grown by the Czochralski (CZ) method. 3 Ga 5 O 12 TGG (TGG)-based materials have been widely used because TGG-based single crystals have a small absorption coefficient for 1 μm laser light.3 Al 5 O 12 The use of TAG (tetrahydroguanidine-glucose)-based materials in optical isolators has also been proposed, because TAG has a high Verdet constant (VC) and may enable smaller devices than TGG.
[0005] For example, Patent Document 1 discloses a seeding method for growing terbium gallium garnet (TGG) single crystals by the Cz method (rotary pulling method), in which a seed crystal is brought into contact with a raw material melt and pulled up to grow (claim 1 in Patent Document 1). Patent Document 1 also describes that TGG crystals are known as crystals with low optical loss, high thermal conductivity, high damage threshold, and high Verdet constant, and are mainly used in rotators and optical isolators for wavelengths from 400 nm to 1100 nm (
[0004] in Patent Document 1).
[0006] Patent Document 2 discloses an optical isolator material that is a terbium-cerium-aluminum-garnet type single crystal in which part of the terbium is replaced by cerium, and describes that a powder raw material is heated and melted, and a seed crystal is pulled up from the resulting solution to grow a terbium-cerium-aluminum-garnet type single crystal (claims 2 and 8 of Patent Document 2). Patent Document 2 also describes that since it contains Ce, which has a larger Faraday rotation angle than terbium, the Faraday rotation angle can be increased, and that it is suitable as a single crystal for an optical isolator in a fiber laser light processing machine (
[0022] ,
[0023] , and
[0077] of Patent Document 2).
[0007] Patent Document 3 discloses ceramics made of terbium aluminum oxide with a light transmittance of 10% or more and an absorption coefficient of 6.4 / cm or less (claim 5 of Patent Document 3). Patent Document 3 also describes that since the ceramics can be produced as a bulk sintered body, it is possible to obtain a mother substrate with a very large area compared to the case of growing a single crystal, and it is possible to obtain multiple pieces, and that the ceramics are useful for magneto-optical devices such as isolators, or magneto-optical sensors such as current sensors (
[0015] and
[0026] of Patent Document 3). [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2013-056785 A [Patent Document 2] JP 2013-230958 A [Patent Document 3] JP 2008-007385 A Summary of the Invention [Problem to be solved by the invention]
[0009] However, the conventional techniques have room for improvement in obtaining Faraday elements for optical isolators with sufficient characteristics at low cost. In other words, conventional Faraday elements are inferior in performance such as Verdet constant (VC), absorption coefficient, and extinction ratio, and are expensive to manufacture. To explain this point, the polarization rotation angle (45°) rotated by the Faraday element (1) is called the Faraday rotation angle (F). The Faraday rotation angle (F) can be calculated according to the following formula (1) using the Verdet constant (VC) of the Faraday element, the optical path length (element length; L), and the magnetic field strength (H).
[0010]
number
[0011] In order to promote the widespread use of optical isolators, it is essential to reduce the size and cost of the Faraday elements used in them. To achieve this, it is necessary to increase the Verdet constant (VC) of the Faraday element. If the Verdet constant is small, the optical path length (L) and magnetic field strength (H) required to obtain the Faraday rotation angle (F=45°) must be increased. In other words, to increase the optical path length, a large Faraday element must be used, and to increase the magnetic field strength, a large magnet must be used. Both of these lead to larger elements and higher costs.
[0012] In addition, Faraday elements are required to have a small absorption coefficient and a large extinction ratio. If the absorption coefficient is large, the light loss during passage through the Faraday element becomes large, making highly efficient laser processing difficult. The extinction ratio is the ratio of the propagation loss suffered by forward light to the propagation loss suffered by reverse light when a magnetic field is applied. If this ratio is small, the reverse light cannot be blocked sufficiently.
[0013] For example, the TGG single crystal proposed in Patent Document 1 has a small Verdet constant (VC) of 35 rad / T·m. Therefore, there is a limit to miniaturizing and reducing the cost of the element. Patent Document 2 also proposes producing a TAG single crystal by a melt growth method (Czochralski method) using a seed crystal, but TAG is a decomposed melt type crystal. Therefore, the composition is likely to change during crystal growth. If the composition changes, distortion occurs with the crystal growth, which causes a problem of a significant decrease in the extinction ratio. In particular, Ce has a small segregation coefficient (equilibrium distribution coefficient), and it has been difficult to produce a single crystal containing a high concentration of Ce from a melt. In addition, there is a problem that the production cost of single crystals is high.
[0014] Patent Document 3 proposes the preparation of TAG ceramics, but the absorption coefficient of this ceramic is not sufficiently small. In fact, the light absorption coefficient (absorption coefficient) of the ceramic specifically disclosed in Patent Document 3 is at least 2.81 cm for blue light with a wavelength of 408 nm. -1stays at (Table 1 of Patent Document 3). Also, although the TAG has a higher Verdet constant than TGG, it is insufficient for miniaturizing the element by itself.
[0015] In view of such conventional problems, the present inventor has conducted intensive studies. As a result, it has been found that a rare earth aluminum garnet sintered body having a specific composition containing terbium (Tb), cerium (Ce), and aluminum (Al) as constituent components has a high Verdet constant (VC) and extinction ratio and a small absorption coefficient with respect to laser light in the 1-μm wavelength band. It has also been found that this sintered body is inexpensive and can be made large-sized, enabling the production of high-performance and Faraday elements at low cost.
[0016] The present invention has been completed based on such findings, and an object thereof is to provide a rare earth aluminum garnet sintered body having a high Verdet constant (VC) and extinction ratio and a small absorption coefficient with respect to laser light in the 1-μm wavelength band, and a Faraday element including this sintered body. Another object of the present invention is to provide a method for manufacturing the above sintered body and Faraday element at low cost. Furthermore, an object is to provide a magneto-optical element including the above Faraday element.
Means for Solving the Problems
[0017] The present invention includes the following aspects (1) to (9). In this specification, the expression "~" includes the numerical values at both ends. That is, "X~Y" is synonymous with "X or more and Y or less".
[0018] (1) Chemical formula: Tb 3-x Ce x Al 5 O 12 A rare earth aluminum garnet sintered body having a composition represented by (where 0 < x ≦ 0.35).
[0019] (2) The rare earth aluminum garnet sintered body according to (1) above, wherein x satisfies 0.05 ≦ x ≦ 0.30.
[0020] (3) The rare earth aluminum garnet sintered body is the rare earth aluminum garnet sintered body according to (1) or (2) above, having an extinction ratio of 45 dB or more with respect to light having a wavelength of 0.9 to 1.1 μm.
[0021] (4) The rare earth aluminum garnet sintered body is the rare earth aluminum garnet sintered body according to any one of (1) to (3) above, having a Verdet constant (VC) of 60 rad / T·m or more with respect to light having a wavelength of 0.9 to 1.1 μm.
[0022] (5) The rare earth aluminum garnet sintered body is the rare earth aluminum garnet sintered body according to any one of (1) to (4) above, having an absorption coefficient of less than 0.2 cm -1 with respect to light having a wavelength of 0.9 to 1.1 μm.
[0023] (6) A method for producing a rare earth aluminum garnet sintered body having a composition represented by the chemical formula: Tb 3-x Ce x Al 5 O 12 (where 0 < x ≦ 0.3), comprising the following steps; A step of preparing a cerium (Ce) source, a terbium (Tb) source, and an aluminum (Al) source as raw material powders, A step of mixing the raw material powders to obtain a mixed powder having a particle size of 100 to 300 nm, and A step of sintering the mixed powder to obtain a sintered body The method comprising these steps.
[0024] (7) The method according to (6) above, wherein the sintering of the mixed powder is performed by a spark plasma sintering (SPS) method.
[0025] (8) A Faraday element comprising the rare earth aluminum garnet sintered body according to any one of (1) to (5) above.
[0026] (9) A magneto-optical element comprising the Faraday element according to (8) above.
Advantages of the Invention
[0027] According to the present invention, there are provided a rare earth aluminum garnet sintered body having a high Verdet constant (VC) and extinction ratio and a small absorption coefficient with respect to laser light in the 1-μm wavelength band, and a Faraday element including this sintered body. Further, according to the present invention, there is provided a method for manufacturing the above sintered body and Faraday element at low cost. Furthermore, there is provided a magneto-optical element including the above Faraday element.
Brief Description of the Drawings
[0028] [Figure 1] It is a schematic cross-sectional view showing the configuration of a sintering mold used in the discharge plasma sintering method. [Diagram 2] It is a diagram showing an example of the X-ray diffraction profile of the sintered body.
Embodiments for Carrying Out the Invention
[0029] [Rare Earth Aluminum Garnet Sintered Body] The rare earth aluminum garnet sintered body of the present embodiment (hereinafter, may be collectively referred to as "sintered body") has a composition represented by the chemical formula: Tb 3-x Ce x Al 5 O 12 Here, x satisfies 0 < x ≤ 0.35.
[0030] This embodiment is directed to a sintered body. Unlike single crystals and thin films, sintered bodies are bulk polycrystalline bodies. Unlike single crystals, sintered bodies, which are bulk polycrystalline bodies, do not have long-range order. Therefore, even if the composition of each grain is shifted, no distortion occurs due to crystal growth. Therefore, a high extinction ratio can be obtained. In addition, sintered bodies can be made from inexpensive raw materials and can be made large. Large sintered bodies can be manufactured in bulk by cutting out a large number of elements from them. Therefore, the manufacturing cost per element can be reduced. Furthermore, sintered bodies have a large degree of freedom in composition and shape. In contrast, single crystals and thin films require expensive raw materials and manufacturing equipment, and cannot be obtained at low cost. In addition, when depositing single crystals or thin films on a substrate, they need to be matched with the lattice constant of the substrate, and there is a problem that the degree of freedom in composition and shape is small. Furthermore, single crystals are prone to distortion due to crystal growth, which may deteriorate the extinction ratio. In particular, Ce has a small segregation coefficient (equilibrium distribution coefficient), and it is difficult to manufacture single crystals containing Ce at a high concentration from a melt.
[0031] The sintered body of this embodiment has the chemical formula: Tb 3-x Ce x Al 5 O 12 In other words, it is made of terbium aluminum garnet (TAG) in which part of the terbium (Tb) is replaced with cerium (Ce). Terbium aluminum garnet (TAG) has a garnet-type crystal structure. In terbium aluminum garnet, the terbium ion (Tb 3+ ) is surrounded by an oxygen dodecahedron. Five aluminum ions (Al 3+ ) three of them occupy sites surrounded by oxygen tetrahedra, and the remaining two occupy sites surrounded by octahedra. TAG does not contain magnetic ions and is a paramagnetic material. In the stoichiometric composition of rare earth aluminum garnet, the molar ratio of (Tb+Ce) to Al is 3:5, but the sintered body of this embodiment does not need to have a strict stoichiometric composition. 。
[0032] In the sintered body of this embodiment, the Ce content (x) satisfies 0 < x ≤ 0.35. When a part of terbium (Tb) is replaced with cerium (Ce), the Verdet constant (VC) increases without decreasing the extinction ratio and absorption coefficient. x may be 0.05 or more, may be 0.10 or more, and may be 0.20 or more. On the other hand, if the amount of cerium is excessively large, the garnet crystal structure becomes unstable, and heterogeneous phases such as cerium oxide (CeO 2 ) are generated. Such heterogeneous phases have a refractive index different from that of garnet. Therefore, the heterogeneous phases contained in the garnet phase may cause light scattering and impair transparency. x may be 0.30 or less, may be 0.20 or less, and may be 0.10 or less.
[0033] Preferably, the sintered body has a Verdet constant (VC) of 60 rad / T·m or more with respect to light having a wavelength of 0.9 to 1.1 μm. In fiber laser processing, high-power lasers in the wavelength band of 1 μm (0.9 to 1.1 μm) are frequently used. Therefore, by increasing the Verdet constant in this wavelength band, the optical path length of the Faraday element can be shortened. Further, by shortening the optical path length, light loss can be further suppressed. The Verdet constant may be 80 rad / T·m or more, may be 100 rad / T·m or more, may be 120 rad / T·m or more, may be 140 rad / T·m or more, may be 160 rad / T·m or more, and may be 180 rad / T·m or more. The higher the Verdet constant, the more preferable, and its upper limit is not limited. However, typically it is 200 rad / T·m or less.
[0034] Preferably, the sintered body has an extinction ratio of 45 dB or more with respect to light having a wavelength of 0.9 to 1.1 μm. The extinction ratio is the ratio of the propagation loss received by the forward light to the propagation loss received by the backward light when a magnetic field is applied. When this ratio is large, the forward light is sufficiently transmitted and the backward light is sufficiently blocked. Therefore, the blocking performance of the optical isolator is improved. The extinction ratio may be 46 dB or more, may be 47 dB or more, and may be 48 dB or more. The higher the extinction ratio, the more preferable, and its upper limit is not limited. However, typically it is 55 dB or less.
[0035] Preferably, the sintered body has an absorption coefficient of 0.2 cm for light having a wavelength of 0.9 to 1.1 μm. -1 The absorption coefficient is an index of light loss, and the smaller this value is, the smaller the light loss is.
[0036] death However, the presence of other phases can impair the beneficial effects based on the garnet phase. For example, cerium oxide (CeO 2 ) have a different optical refractive index from garnet. Therefore, if such a heterophase is present, it may cause light scattering and increase the optical loss (absorption coefficient). Therefore, it is preferable that the sintered body is made of only a single phase of rare earth aluminum garnet. The presence of a heterophase can be evaluated by analyzing the sintered body by X-ray diffraction and examining the resulting diffraction pattern. Specifically, if no diffraction peaks due to the heterophase are observed or the peak intensity is below the background level, it can be considered that no heterophase is present. In addition, if the absorption coefficient for light with wavelengths of 0.9 to 1.1 μm is 0.2 cm -1 If it is less than this, it can be considered that no other phase is present.
[0037] Te Rubium (Tb) and aluminum (Al) may be replaced by other rare earth elements (R) or gallium (Ga). However, if other elements are contained in large amounts, the advantageous effects based on the garnet phase may be impaired. Therefore, the lower the content of other elements, the better. The sintered body may have a composition containing cerium (Ce), terbium (Tb), aluminum (Al) and oxygen (O), with the remainder being unavoidable impurities. The unavoidable impurities are impurities derived from raw materials or impurities that are inevitably mixed in during the manufacturing process, and their content is typically 1000 ppm or less.
[0038] [Method of manufacturing rare earth aluminum garnet sintered body] The manufacturing method of the sintered body of this embodiment is not limited as long as the sintered body satisfies the above-mentioned requirements. However, a suitable manufacturing method includes the following steps: a step of preparing a cerium (Ce) source, a terbium (Tb) source, and an aluminum (Al) source as raw material powders (preparation step), a step of mixing the prepared raw material powders to obtain a mixed powder having a particle size of 100 to 300 nm (mixing step), and a step of sintering the obtained mixed powder to obtain a sintered body (sintering step). Details of each step are described below.
[0039] <Preparation process> In the preparation step, a cerium (Ce) source, a terbium (Tb) source, and an aluminum (Al) source are prepared as raw material powders. The raw material powders are not particularly limited as long as they form a garnet phase in the subsequent sintering step. For example, compounds such as oxides, carbonates, hydroxides, nitrates, and / or alkoxides of garnet constituents (Ce, Tb, Al) can be used. The raw materials may contain a single garnet constituent, or may contain a combination of multiple constituents in the form of a composite compound.
[0040] <Mixing process> In the mixing step, the prepared raw material powders are mixed to produce a mixed powder with a particle size of 100 to 300 nm. The mixing ratio of the raw materials may be adjusted so that the final sintered body has the desired composition. However, in order to improve the transparency of the sintered body, it is necessary to increase the density, and for this purpose, the smaller the particle size of the mixed powder, the better. However, as the particle size becomes smaller, aggregation becomes more likely to occur, so it is preferable to set the particle size to 100 to 300 nm. If the particle size and its particle size distribution are large, it is difficult to increase the density of the sintered body.
[0041] The method for adjusting the particle size of the mixed powder is not particularly limited. The particle size of the mixed powder may be adjusted by using fine raw material powder. Alternatively, the particle size may be adjusted by using coarse raw material powder and pulverizing it when mixing. However, in order to obtain a transparent sintered body, it is essential to suppress the inclusion of impurities to 1000 ppm or less, so it is preferable to prevent contamination from a pulverizer or the like during pulverization.
[0042] The mixing method is not particularly limited, and may be either dry or wet. In the case of wet mixing, a step of drying the mixed powder may be provided. The mixing device is also not particularly limited, and may be a mixer such as a mortar, a mortar and a Henschel mixer, or a mixer and grinder such as a ball mill and an attritor.
[0043] <Sintering process> In the sintering process, in general sintering, a powder that will be a single garnet phase is synthesized and used as the sintering raw material, so as long as the desired sintered body can be obtained, sintering may be performed by a known method. For example, room temperature sintering, gas pressure sintering, hot pressing (HP), hot isostatic pressing (HIP), spark plasma sintering (SPS), etc. can be mentioned. However, SPS is extremely suitable for reactive sintering, which omits the synthesis process of the powder that will be a single garnet phase and mixes oxide powders of Ce, Tb, and Al and reacts them during sintering to form the garnet phase. SPS usually applies a high pressure of over 50 MPa to the sintering raw material in a uniaxial manner, passes a direct current pulse current through a carbon sintering mold, and directly heats the sintering raw material, so that thermal, mechanical, and electromagnetic energy work in a combined manner to activate the sintering, making the above-mentioned reactive sintering possible. In addition to completing sintering 20 to 100 times faster than other sintering methods, it is also extremely suitable for producing transparent bodies that do not tolerate impurities because it does not require sintering aids.
[0044] SPS will be explained in detail. Figure 1 shows a cross-sectional view of the structure of the SPS sintering mold (20). The cylinder (21) and the upper and lower punches (22) are made of carbon. The lower punch (22) is inserted into the cylinder (21), and the sintering material (23) is filled and pressed down by the upper punch (22). This is set in the SPS sintering device, pressure is applied to the punch (22), and electricity is passed from the punch through the cylinder to the punch, and the sintering material is heated while applying uniaxial pressure to the sintering material, and sintering proceeds. The parameters to be controlled in SPS are the heating rate, holding temperature (attained temperature), holding time, and pressure. The heating rate is generally 50 to 100°C / min, and if it is slower than that, the advantage of the rapid sintering of SPS is diminished. The holding temperature is several tens of degrees higher than the temperature at which the displacement sensor of the punch of the device switches from contraction (during sintering) to expansion, generally about 50°C higher. Since sintering is not complete at the temperature at which contraction switches to expansion, the temperature is raised to a higher temperature than that. Generally, sintering is completed after a holding time of about 20 minutes. However, if the temperature at which the material changes from contraction to expansion is close to the melting point, the holding temperature should be 50°C or less and the holding time should be longer than 20 minutes. The higher the pressure applied, the more dense the sintered body will be with suppressed grain growth, but the limit for carbon sintering molds is generally set at 100 MPa.
[0045] In particular, the SPS method is suitable for producing the sintered body of this embodiment. That is, this sintered body contains cerium (Ce) in the garnet phase. For cerium to exist stably in the garnet, it must be present as a trivalent ion (Ce 3+ However, in the atmosphere, cerium (Ce) is converted into a trivalent ion (Ce 3+ ) to tetravalent ions (Ce 4+ ) is more stable. Therefore, in the usual sintering method, cerium oxide (CeO 2 ), which tends to produce heterogeneous phases, making it difficult to produce a garnet sintered body in a single phase. By contrast, SPS sintering can produce a sintered body without heterogeneous phases. The details of why this is the case are unclear, but the particle surface is activated to a high electron state by plasma discharge, resulting in the formation of trivalent ions (Ce 3+ ) is more easily maintained.
[0046] After the sintering step, the sintered body may be washed or processed as necessary. Examples of processing include grinding or polishing both sides of the sintered body. This makes it possible to obtain a sintered body with a smooth surface and little surface light scattering.
[0047] In this way, the terbium aluminum garnet sintered body of this embodiment is produced. The obtained sintered body is characterized by a high Verdet constant (VC) because of sufficient substitution of cerium (Ce). In addition, there are few heterogeneous phases and vacancies, and the extinction ratio is high and the optical loss (absorption coefficient) is suppressed. In addition, the manufacturing cost is low and the size can be increased, so that the element can be obtained inexpensively.
[0048] <Faraday element> The Faraday element of this embodiment includes the rare earth aluminum garnet sintered body described above. The Faraday element may have a known configuration as long as it includes the above-mentioned sintered body. For example, the Faraday element may have a configuration including a sintered body and an anti-reflective coating formed on both sides of the sintered body.
[0049] The Faraday element of this embodiment is equipped with a sintered body having a high Verdet constant (VC), so that the element length (optical path length) can be made small. In other words, even if the element length is made small, the required Faraday rotation angle (45°) can be obtained. In addition, the optical absorption coefficient is small, so the optical loss is small. Furthermore, since there is no need to use single crystals or thin films, which have high manufacturing costs, it is inexpensive.
[0050] The Faraday element may have a Verdet constant (VC) for light with a wavelength of 0.9 to 1.1 μm of 60 rad / T·m or more, 80 rad / T·m or more, 100 rad / T·m or more, 120 rad / T·m or more, 140 rad / T·m or more, 160 rad / T·m or more, or 180 rad / T·m or more. The Faraday element may have an extinction ratio for light with a wavelength of 0.9 to 1.1 μm of 45 dB or more, 46 dB or more, 47 dB or more, or 48 dB or more. The Faraday element may have an absorption coefficient for light with a wavelength of 0.9 to 1.1 μm of 0.2 cm -1 It may be less than.
[0051] <Magneto-optical elements> The magneto-optical element of this embodiment includes the above-mentioned Faraday element. An example of such a magneto-optical element is an optical isolator for a fiber laser. The optical isolator including the Faraday element of this embodiment can be miniaturized and has excellent performance. Moreover, it can be manufactured at low cost.
[0052] The magneto-optical element of this embodiment is not limited to an optical isolator for a fiber laser. It may be an optical isolator for optical communication, or may be an optical circulator, an optical attenuator, an optical switch, an optical modulator, or other magneto-optical element, or a current sensor or other magneto-optical sensor. It goes without saying that the use of the Faraday element of this embodiment can realize high performance and low cost of these elements. EXAMPLES
[0053] The present invention will be described in more detail with reference to the following examples and comparative examples, but the present invention is not limited to the following examples.
[0054] (1) Preparation of sintered body [Example 1 to Example 6] In Examples 1 to 6, Tb 3-x Ce x Al 5 O12 Sintered bodies were produced by changing the composition within the range of x=0.00 to 0.40.
[0055] First, the raw material is cerium oxide (CeO 2 ) powder, terbium oxide (Tb 4 O 7 ) powder and aluminum oxide (Al 2 O 3 ) powders were prepared, and these powders were weighed and mixed so as to obtain the composition in Table 1. The mixed powder obtained was then subjected to a ball mill treatment using zirconia balls to produce a sintering raw material powder with a particle size of 100 to 300 nm. The particle size (particle size distribution) of the sintering raw material powder was measured by dynamic light scattering (DLS).
[0056] The obtained sintering raw material powder was subjected to spark plasma sintering (SPS) to produce a sintered body. The sintering mold (20) shown in FIG. 1 was used for sintering. First, 500 g of sintering raw material powder (23) was filled into the carbon cylinder (inner diameter 75 mm; 21) of the sintering mold, and the top and bottom were pressed with carbon punches (22). The sintering mold (20) filled with the sintering raw material powder was set in a spark plasma sintering device (not shown), and then sintering was performed by applying pressure of 100 MPa to the carbon punch (22). The sintering conditions were as follows:
[0057] - Heating rate: 100℃ / min -Achieved temperature: 1600℃ -Holding time: 20 minutes -Vacuum degree: 5×10 -2 Pa
[0058] The optical surface of the obtained sintered body (the surface in contact with the punch 2) was polished to prepare a measurement sample. t It was.
[0059] [Example 7] In Example 7, Tb 3 Ga 5 O 12A (TGG) single crystal was prepared by the Czochralski (CZ) method and used as the measurement sample.
[0060] (2) Evaluation For the samples obtained in Examples 1 to 7, various properties were evaluated as follows.
[0061] <xrd> The crystal phase of each sample was examined by X-ray diffraction (XRD) under the following analytical conditions:
[0062] - Equipment: X'Part-PRO (PANanalytical) - Target: Cu - X-ray output settings: 40mA, 45kV -Injection beam module: θ-2θ scan - Mask [mm]: fixed, 15 - Divergence slit [DS°2Th.]: PDS, fixed, 1 / 2 -Scattering slit [DS°2Th.]: PASS, fixed, 1 / 2 -Start angle [°2Th.]: 10 - End angle [°2Th.]: 120 - Scan step time [s]: 22 - Filter: Nickel - Detector: X'Celerator (semiconductor array detector) -Solar slit: 0.02 - Sample Spinner: Pause
[0063] <Structural Observation> The microstructure of the sintered body was observed using a scanning electron microscope (SEM) at an accelerating voltage of 5.0 kV and a magnification of 20.0 kV.
[0064] <Absorption coefficient> The absorption coefficient of each sample was obtained using a spectrophotometer. Specifically, the wavelength dispersion of the light transmittance of the sample was measured using the spectrophotometer, and the light transmittance (T) and absorption coefficient (α) in the 1 μm wavelength band were calculated using the obtained measurement data according to the following formulas (2) and (3). In the following formulas (2) and (3), L is the thickness of the medium, Pin is the incident light power, and Pout is the transmitted light power.
[0065]
number
number
[0066] <Verdet constant and extinction ratio> The Verdet constant (VC) and extinction ratio of each sample were measured using a magneto-optical measuring device. The magneto-optical measuring device was equipped with a light source and a photodetector that detects the laser light from the light source, and further equipped with a polarizer and a measuring piece between the light source and the photodetector. The light source was a Nd:YVO 4 A laser was used. A Glan-Thompson prism with an extinction ratio of over 60 dB was used as the polarizer. The two polarizers were arranged in a crossed Nicol configuration. The beam diameter of the laser light was set to 0.6 mm, which is the diameter used in general optical isolators.
[0067] First, a rod with a size of φ3×L10 mm was cut out from the sample to prepare a measurement piece. Next, the measurement piece was inserted into an optical measurement device, and laser light was irradiated from a light source. The intensity of the laser light transmitted through the polarizer and the sample piece was measured with a photodetector. One side of the polarizer was rotated while irradiating the laser light L, and the change in light intensity was obtained. Then, the extinction ratio was calculated according to the following formula (4) using the minimum (Imax) and maximum (Imax) of the light intensity.
[0068]
number
[0069] In addition, a magnetic field was applied parallel to the direction of travel of the laser light using an electromagnet to measure the Faraday rotation angle θ. The Verdet constant (VC) was calculated according to the following formula (5). In the formula (5), L is the length of the measurement piece (10 mm) and H is the magnetic field strength.
[0070]
number
[0071] (3) Results The evaluation results obtained for Examples 1 to 7 are shown in Table 1. Examples 2 to 6 are embodiment samples, and Examples 1 and 7 are comparative examples. The X-ray diffraction (XRD) profile of the sintered body produced in Example 1 is shown in Figure 2 together with the standard diffraction peaks of the JSPDS card (01-088-2047).
[0072] <xrd> As shown in Table 1, the sintered bodies of Examples 1 to 5, in which the Ce content x was 0.00 to 0.30, were composed of only a single garnet phase. In fact, as shown in FIG. 2, in the sintered bodies, peaks due to the garnet phase (TAG) were observed, but peaks due to other phases were not observed. On the other hand, the sintered body of Example 6, in which x was 0.40, contained cerium oxide (CeO 2 ) was observed.
[0073] <Absorption coefficient> As shown in Table 1, the sintered bodies of Examples 1 to 5 have an absorption coefficient of 0.2 cm -1 On the other hand, the sintered body of Example 6 was not transparent, although it was translucent. Even if a large amount of Ce was added, it could not be accommodated in the Tb site, and the CeO 2 This precipitated in the sintered body in the form of , which became a base for light reflection and impaired transparency.
[0074] <Structural Observation> Microstructural observation revealed that the crystal grains were relatively uniform in size, ranging from 200 to 800 nm, and the sintered body was dense with almost no voids observed.
[0075] <Verdet constant and extinction ratio> As shown in Table 1, the greater the Ce content x, the higher the Verdet constant (VC), reaching an extremely high value of VC = 183 rad / T m at x = 0.30. The extinction ratio was almost constant. As a result, in the region of 0.05≦x, the Verdet constant was more than twice as high as that of TGG single crystal, and the extinction ratio was also so high that it would be difficult to achieve with TGG single crystal.
[0076] In general, the extinction ratio is affected by the distortion of the crystal. In conventional single crystals, even slight variations in composition cause distortion of the single crystal, worsening the extinction ratio. In contrast, polycrystalline bodies (sintered bodies) made using the spark plasma sintering method have uniform grain units, and are presumably in a state in which distortion deviation is less likely to occur. For this reason, it is believed that the extinction ratio has been significantly improved compared to single crystals.
[0077] [Table 1] [Explanation of symbols]
[0078] 20 Sintering mold 21 Cylinder 22 Punch 23 Sintering materials< / xrd> < / xrd>
Claims
1. Chemical formula: Tb 3-x C.E. x A 5 O 12 (wherein x satisfies 0.05≦x≦0.30), The extinction ratio for light with a wavelength of 0.9 to 1.1 μm is 45 dB or more, The Verdet constant (VC) for light having a wavelength of 0.9 to 1.1 μm is 60 rad / T·m or more; A rare earth aluminum garnet sintered body having an absorption coefficient of less than 0.2 cm -1 for light having a wavelength of 0.9 to 1.1 μm.
2. Chemical formula: Tb 3-x C.E. x A 5 O 12 A method for producing a rare earth aluminum garnet sintered body having a composition represented by the formula (where x satisfies 0.05≦x≦0.30), comprising the steps of: preparing a cerium (Ce) source, a terbium (Tb) source, and an aluminum (Al) source as raw material powders; mixing the raw material powders to obtain a mixed powder having a particle size of 100 to 300 nm; and A step of sintering the mixed powder to form a sintered body. and sintering the mixed powder by a spark plasma sintering (SPS) method.
3. A Faraday element comprising the rare earth aluminum garnet sintered body according to claim 1.
4. A magneto-optical element comprising the Faraday element according to claim 3.
Citation Information
Patent Citations
Light transmitting ceramic and method for producing the same
JP2002326862A
Fluorescent material of tag-type magnetoptical crystal and its manufacturing method
JP2004300409A
Manufacturing method of ceramics comprising terbium / aluminum oxide and ceramics comprising terbium / aluminum oxide manufactured by the same
JP2008007385A
Seeding method in TGG single crystal growth
JP2013056785A
Optical isolator material, method for producing the same, optical isolator, and optical processing apparatus
JP2013230958A